How Identity Enriches and Complicates the Research Process: Reflections from Political Ecology Fieldwork - Nyantakyi-Frimpong, Hanson (The Professional geographer, 2021)
Among political ecologists, long-term ethnographic immersion is one of the key approaches to conducting fieldwork. This article reflects on how a researcher's identity enriches or complicates the immersed fieldwork process. Drawing on fieldwork in West Africa, it illuminates the challenges confronted when men conduct research into women's experiences. It sheds specific light on effects on the data gathering process, the data gathered, and ethical concerns. Overall, the article suggests why political ecologists need to seriously consider issues around fieldworkers' identity and the quality of fieldwork relations with research subjects. Central to the reflections here are issues concerning hermeneutic complexities, especially when research assistants are relied on to understand the everyday, embodied, and emotional aspects of nature-society relations. The article argues that although local-level social relations have long been part of political ecology research, the ability to undertake fieldwork itself is also shaped by researcher-researched social relations that are often less recognized. Although these reflections provide lessons for political ecology research more broadly, the insights here particularly seek to inform emerging work on "new" feminist political ecology, which tends to focus on data collection at less visible scales, particularly the body and the household.